A unique choline nitrate-based organo-aqueous electrolyte enables carbon/carbon supercapacitor operation in a wide temperature window (−40°C to 60°C) - Supiyeva, Zhazira; Mansurov, Zulkhair; Azat, Seitkhan; Abbas, Qamar (Frontiers in Chemistry, 2024)
Some drawbacks of aqueous electrolytes such as freezing at low temperatures and extensive evaporation at high temperatures restrict their industrial viability. This article introduces a stabilized neutral aqueous choline nitrate electrolyte with 10 vol.% methanol additive which improves the temperature stability of electrolyte via enhanced hydrogen bonding with choline cation and water and keeps the good state-of-health of the supercapacitor cells under extreme operating conditions. The symmetric carbon/carbon supercapacitor in 5 mol/kg choline nitrate + 10 vol.% methanol (σ = 76 mS/cm at 25˚C) exhibits 103 F/g at room temperature during galvanostatic charge/discharge up to 1.5 V, which decreases to 78 F/g at -40˚C due to the suppressed faradaic reactions occurring at the carbon electrode. However, under similar charge/discharge conditions, the capacitance increases to 112 F/g when the supercapacitor operates at 60˚C. This capacitance increase at high temperatures is due to the faradaic reactions related to enhanced hydrogen adsorption and desorption. The most remarkable aspect of proposed supercapacitor is its ability to keep capacitance and power performance during high voltage floating at 1.5 V at three tested temperatures (-40˚C, 24˚C and 60˚C).